2001
DOI: 10.1177/0020852301671008
|View full text |Cite
|
Sign up to set email alerts
|

Pride and Performance in African Public Services: Analysis of Institutional Breakdown and Rebuilding Efforts in Nigeria and Uganda

Abstract: Pride in public service is inextricably linked to institutional performanceespecially in countries like Nigeria and Uganda, where the state is as yet not fully institutionalized or even legitimized. Despite their colonial origins and the challenges which confront the modern state in Africa, the Nigerian and Ugandan civil services functioned well in terms of their primary responsibilities. They proffered policy advice, regulated their nascent economies and societies and delivered high-quality services to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…This objective can only be realized through aggregate fiscal discipline in the cause of using the concept of decentralization among the three tiers of government. It is equally observed that budget outcomes on the delivery of primary education and healthcare service by local government administration is not optimally realized, there are other researchers such as (Lawal, 2000;Olowu, 2001;Ajayi, 2002;Akindele, 2004;Awotokun, 2005) who lend credence to the findings of this study by saying that local governments most often do not spend what is approved for service delivery in the budget, ISSN 2161-7104 2012 www.macrothink.org/jpag 54 instead they prefer to divert resources to other programs in the name of virement.…”
Section: Resultsmentioning
confidence: 99%
“…This objective can only be realized through aggregate fiscal discipline in the cause of using the concept of decentralization among the three tiers of government. It is equally observed that budget outcomes on the delivery of primary education and healthcare service by local government administration is not optimally realized, there are other researchers such as (Lawal, 2000;Olowu, 2001;Ajayi, 2002;Akindele, 2004;Awotokun, 2005) who lend credence to the findings of this study by saying that local governments most often do not spend what is approved for service delivery in the budget, ISSN 2161-7104 2012 www.macrothink.org/jpag 54 instead they prefer to divert resources to other programs in the name of virement.…”
Section: Resultsmentioning
confidence: 99%
“…There is documented evidence that this institution served its purpose. For instance, a comparative assessment of Nigerian and Ugandan civil services (both located in the western and eastern segments of the continent) showed how these two countries' civil services contributed commendably to economic growth and good governance both before and immediately after political independence (Olowu, 2001). Olowu contrasted their performance in the 1960-70 decade with their performance in the 1990s and demonstrated a severe decline.…”
Section: African Civil Service's Contribution To Development and Good Governance And The Csr Paradoxmentioning
confidence: 99%
“…The findings of Hill and Lynn (2005) support the view that the shift away from hierarchical government towards horizontal government represents only a tactical shift but that this is basically within a system of constitutional authority that remains hierarchical. Olowu (2001) argues that, in the case of Africa, states confront new challenges in the 21st century. These are the two old challenges of nation-building and state maintenance and new ones of competition and democratisation in a globalising world.…”
Section: Conceptualising the Institutions And Activities Supporting Gmentioning
confidence: 99%